Non-dominant hemisphere stroke and spatial neglect: is stimulation of known hobbies and cravings a way to make rehabilitation more effective? - T. Juška; A. Vaitkus; M. E. Klinke; V. Matijošaitis (Neurologijos seminarai)
Stroke is an acute neurologic injury that occurs because of brain ischemia or brain hemorrhage. Improved treatment options for stroke have increased patient survival, but the condition remains the leading cause of long-term disability worldwide. The huge costs and adverse impact of post-stroke disability make improving rehabilitation strategies a priority. Spatial neglect (SN) is characterized as a condition in which patients display insufficient attention to the contralesional side of their surroundings and their own body. It is the most common neurocognitive disorder causing long-term disability, occurring in approximately half of patients with stroke in the non-dominant brain hemisphere. Typical adjacent consequences of SN are difficulties with attention, perception, learning, memory, recognition, motivation, and expression of emotions. Numerous rehabilitation techniques have been designed to alleviate and remediate symptoms of SN. Paradoxically, many of these techniques have not found their way into routine clinical bedside rehabilitation. Rehabilitators may be reluctant to implement unfamiliar strategies, especially if they are new, controversial, or not tested in a clinical environment. In this paper, we propose a hypothesis that better rehabilitation results for stroke survivors with SN can be reached by including patients’ hobbies and cravings when training attention towards the neglected space during rehabilitation. Patients’ unique cravings and hobbies when used as conditioned cueing may help boost the mesolimbic dopamine system and eliminate hemispheric imbalance, which is thought by many to cause SN.